The ambiguous victim: Miklós Nyiszli's narrative of medical experimentation in Auschwitz-Birkenau - Turda, Marius (Historein, 2014)
While recent scholarship has – for the past two decades – endeavoured to transcend initial reservations about memoirs of Holocaust survivors, the difficulty with some of these memoirs – namely their authors’ implicit complicity in unethical medical research and in the Nazi Holocaust in general – remains however problematic. To address this thorny issue, this article considers the memoirs of a Jewish inmate doctor, Miklós Nyiszli, who worked with and for SS medical officers in Auschwitz, and his Auschwitz: A Doctor’s Eyewitness Account. His memoirs can help us understand wider truths about the “bond of complicity” that, according to Primo Levi, existed between perpetrators and victims in the Nazi concentration camp.